Streptococcus suis Serotype 2 Biofilms Inhibit the Formation of Neutrophil Extracellular Traps - Ma, Fang; Yi, Li; Yu, Ningwei; Wang, Guangyu; Ma, Zhe; Lin, Huixing; Fan, Hongjie (Frontiers in Cellular and Infection Microbiology, 2017)
Invasive infections caused by Streptococcus suis serotype 2 (SS2) has emerged as a clinical problem in recent years. Neutrophil extracellular traps (NETs) are an important mechanism for the trapping and killing of pathogens that are resistant to phagocytosis. Biofilm formation can protect bacteria from being killed by phagocytes. Until now, there have only been a few studies that focused on the interactions between bacterial biofilms and NETs. SS2 in both a biofilm state and a planktonic cell state were incubated with phagocytes and NETs, and bacterial survival was assessed. DNase I and cytochalasin B were used to degrade NET DNA or suppress phagocytosis, respectively. Extracellular DNA was stained with impermeable fluorescent dye to quantify NET formation. Biofilm formation increased up to 6-fold in the presence of neutrophils, and biofilms were identified in murine tissue. Both planktonic and biofilm cells induced neutrophils chemotaxis to the infection site, with neutrophils increasing by 85.1 and 73.8%, respectively. The bacteria in biofilms were not phagocytized. The bactericidal efficacy of NETs on the biofilms and planktonic cells were equal; however, the biofilm extracellular matrix can inhibit NET release. Although biofilms inhibit NETs release, NETs appear to be an important mechanism to eliminate SS2 biofilms. This knowledge advances the understanding of biofilms and may aid in the development of treatments for persistent infections with a biofilm component.